تأثير الذكاء العاطفي في الأداء الأكاديمي لدى الطلاب الدوليين.. جامعة السلطان الشريف علي الإسلامية : The Effect of Emotional Intelligence on The Academic Performance of International Students -Sultan Sharif Ali Islamic University as a Model- - Abuhalib, Nahil (Journal Al-Muqaddimah, 2023)
Due to the importance of emotional intelligence and its connection to many areas of life, experts have made it a subject of study and interest. Emotional intelligence is the motivation to feel, think, learn, solve problems, make decisions, and control and manage emotions. Based on that, the researchers in this study are trying to find out if there is an effect of intelligence. Emotional impact on academic performance among international students, taking Sultan Sharif Ali Islamic University in Brunei as a model. The research relied on the descriptive analytical method. The research showed several results, the most important of which are: that international students at Sultan Sharif Ali Islamic University have a high level of emotional intelligence. The results also showed that emotional intelligence has a strong and positive fundamental impact on the academic performance of international students.